A Comparative Analysis of Aluminium and Mild Steel on CNC Milling Using CAD/CAM Programming - Wonga@Wanga, Wani; Mohd Sihat, Mohd Zul Haffizi; Hehsan, Haffidzudin (Progress in Engineering Application and Technology, 2024)
The goal of this project is to evaluate machining time and surface roughness for aluminum and mild steel with varying spindle speeds. This study focuses on the comparison of aluminum and mild steel for CNC milling operations utilizing CAD/CAM programming. Mastercam software is used to design the 2D and 3D of the sample block, and simulation is used to get a preview of how the toolpath of the machining will look and to gain the expected time for the machining time of each parameter, which are 1000rpm, 1200rpm, 1400rpm, 1600rpm, and 1800rpm with a constant feed rate of 500mm/rev and a constant depth of cut of 0.5mm. As a result, when both aluminium and mild steel are machined using Computer Numerical Control (CNC), aluminium is likely to be more suitable since the quality of its surface roughness is better than mild steel and the machining time is also shorter.